ENERGY DECAY OF A LINEAR HYPERBOLIC EQUATION WITH LOCALLY DISTRIBUTED DAMPING - Cabanillas Lapa, Eugenio (2002)
Decay estimates for the energy are derived for a linear hyperbolic equation with time - dependent coefficients.